Pedagogik Multiliterasi: Paradigma Pembelajaran dalam Konteks Kurikulum Merdeka - Santi Winangsih; Yusuf Tri Herlambang; Tatang Muhtar (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
In the present day, where technology aligns with the advancement of time, a crucial challenge in the field of education is how to link the curriculum to the needs of the era along with its development. Multiliteracy pedagogy is expected to offer a new perspective to address the demands of the 21st century. The purpose of this research is to examine comprehensively and critically by relating relevant theories to the presence of multiliteracy pedagogy for learning based on the independent curriculum, while also addressing the challenges or demands of the times. The method used is literature study, employing techniques for gathering information and references related to the topic discussed in the research. This study concludes that multiliteracy pedagogy is considered highly relevant in promoting high-order thinking skills, critical thinking, complex problem-solving, and enhancing digital literacy, creativity, and collaboration—essential aspects in the development of the 21st century.